Integration Of Quality, Occupational Safety And Health, And Environmental Management Systems In PT XYZ's Testing Laboratory - Bekti Dwisepti Mafiana; D.S. Priyarsono; Widodo Ramadyanto (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
The Separate Management System implemented in PT XYZ's testing laboratory required a lot of resources. This research aims to integrate the requirements of quality management systems (ISO 9001 and 17025), occupational safety and health (ISO 45001 and PP50/2012), and the environment (ISO 14001). A risk assessment was carried out and found 10 risks, consisting of 9 operational risks and 1 financial risk. Six risks require further mitigation with the TOPSIS method. PT XYZ can implement a partially Integrated Management System (SMT) strategy with 45 procedures, 20 fully integrated procedures, and 25 partially integrated procedures. The effectiveness evaluation showed a decrease in certification costs by 34.55%, a decrease in third-party audit findings by 71.43%, and a minimization of the amount of documented information by 33.48%. The results of this study are expected to help medium to large businesses that implement various separate management systems to switch to management system integration